Painful Hallux Sesamoid: A Pictorial Review - Shah, Ankur; Patel, Drushi (Indographics, 2022)
Sesamoids are small bony structures that are either partially or completely embedded in a tendon. Sesamoid bones are found at multiple places in body but most common sites are in foot, with the most consistent location being the metatarsophalangeal joint of great toe. Various pathologies affecting the sesamoid bones of hallux can be a cause of long-standing forefoot pain and discomfort. Imaging helps in diagnosis of these conditions at an early stage. Imaging also helps in differentiating these pathologies from normal variants like bipartite sesamoid bone.
Keywords: avascular necrosis; bipartite; great toe; hallux sesamoid; sesamoiditis